Geeked Out : Geeked Out #1 - Skye, Obert (New York : Henry Holt and Company, 2018)
In a post-apocalyptic world, AV (Anti-Violence) Club members Tip, Mindy, Owen, and Xen develop semi-super powers and use them to try to save their middle school.
"Christy Ottaviano Books."
Keywords: Clubs -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Ability -- Fiction; Humorous fiction; Science fiction